The problem of moral hazard and effects of deposit insurance project - Sophio Khundadze (IBSU Scientific Journal (IBSUSJ), 2009)
The paper focuses on the significance of deposit insurance program for the financial system stability and smooth operation of the economy. The issue is very substantial for Georgian banking system, which remains to be the only industry all over the post Soviet area without deposit insurance mechanism in place. Georgian banking system lacks the confidence level of its customers, that probably can be restored by imposition of deposit insurance program. The article compares discussions of different experts and their empirical studies arguing whether or not deposit insurance undermines or promotes banking stability. But the experience shows that it, if carefully and properly designed, facilitates additional economic stability, though the last attempt to implement the program in Georgia failed. The article presents the terms of the project elaborated by the National Bank of Georgia and Financial Committee, and gives some proposals needed to perfect the program taking into consideration the recommendations of different experts.
Keywords: 330; Deposit Insurance; Moral Hazard; Banking; Georgia